Be and Bn stars: Balmer discontinuity and stellar-class relationship. - Cochetti, Yanina Roxana (2020)
A significant number of Be stars show a second Balmer discontinuity (sBD) attributed to an extended circumstellar envelope (CE). The fast rotational velocity of Be stars undoubtedly plays a significant role in the formation of the CE. However, Bn stars, which are also B-type rapidly rotating stars, do not all present clear evidence of being surrounded by circumstellar material.Aims: We aim to characterize the populations of Be and Bn stars, and discuss the appearance of the sBD as a function of the stellar parameters. We expect to find new indices characterizing the properties of CEs in Be stars and properties relating Be and Bn stars.Methods: We obtained low- and high-resolution spectra of a sample of Be and Bn stars, derived stellar parameters, characterized the sBD, and measured the emission in the Hα line.Results: Correlations of the aspect and intensity of the sBD and the emission in the Hα line with the stellar parameters and the V sin i are presented. Some Bn stars exhibit the sBD in absorption, which may indicate the presence of rather dense CEs. Six Bn stars show emission in the Hα line, so they are reclassified as Be stars. The sBD in emission appears in Be stars with V sin i ≲ 250 km s-1, and in absorption in both Be and Bn stars with V sin i ≳ 50 km s-1. Low-mass Be and Bn stars share the same region in the Hertzsprung-Russell diagram. The distributions of rotational to critical velocity ratios of Be and Bn stars corresponding to the current stellar evolutionary stage are similar, while distributions inferred for the zero-age main sequence have different skewness.Conclusions: We found emission in the Hα line and signs of a CE in some Bn stars, which motivated us to think that Bn and Be stars probably belong to the same population. It should be noted that some of the most massive Bn stars could display the Be phenomenon at any time. The similarities found among Be and Bn stars deserve to be more deeply pursued.Based on observations obtained at the Complejo Astronómico El Leoncito (CASLEO), operated under an agreement between the Consejo Nacional de Investigaciones Científicas y Técnicas de la República Argentina, the Secretaría de Ciencia y Tecnología de la Nación and the National Universities of La Plata, Córdoba and San Juan, Argentina.